2021
DOI: 10.1016/j.bbih.2020.100185
|View full text |Cite
|
Sign up to set email alerts
|

Early chronic systemic inflammation and associations with cognitive performance after moderate to severe TBI

Abstract: Background Cognitive dysfunction adversely effects multiple functional outcomes and social roles after TBI. We hypothesize that chronic systemic inflammation exacerbates cognitive deficits post-injury and diminishes functional cognition and quality of life (QOL). Yet few studies have examined relationships between inflammation and cognition after TBI. Associations between early chronic serum inflammatory biomarker levels, cognitive outcomes, and QOL 6-months and 12-months after moderate-to-severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 125 publications
1
9
0
Order By: Relevance
“…Higher proinflammatory burden with IL-6, relative to the antiinflammatory marker IL-10, was shown to be relevant to global TBI recovery. Moreover, the acute-phase cytokine load score predicted cognitive performance in moderate-to-severe TBI patients (66), such that IL-1β, TNF-α, sIL-6R, RANTES, and MIP-1β were negatively associated with cognition. Thus, there is a significant correlation between circulating cytokines and chemokines and worsened patient outcomes.…”
Section: Mechanisms Of Tbi-induced Alterations In Brain-gut Communicationmentioning
confidence: 99%
“…Higher proinflammatory burden with IL-6, relative to the antiinflammatory marker IL-10, was shown to be relevant to global TBI recovery. Moreover, the acute-phase cytokine load score predicted cognitive performance in moderate-to-severe TBI patients (66), such that IL-1β, TNF-α, sIL-6R, RANTES, and MIP-1β were negatively associated with cognition. Thus, there is a significant correlation between circulating cytokines and chemokines and worsened patient outcomes.…”
Section: Mechanisms Of Tbi-induced Alterations In Brain-gut Communicationmentioning
confidence: 99%
“…Ferulic acid is preclinically found in vivo with neuroprotective action, as shown in animal reports (Wang et al, 2021 ). Other pieces of evidence proved that TBI can trigger penetrating lesions in astroglia and microglia and cause inflammatory development (Milleville et al, 2020 ). Current GO findings indicated that some of the top BP categories was involved in the effective modulation of neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Key words: biomarker, disorders of consciousness, minimally conscious state, traumatic brain injury miRNA, vegetative state P ERSONS EXPERIENCING SEVERE TRAU-MATIC BRAIN INJURY (TBI) and remaining in states of disordered consciousness (DoC), after acute medical care, are evaluated with neurobehavioral tests to distinguish between states of DoC and to inform rehabilitation management. 1 When considering the heterogeneity of primary and secondary brain damage triggered by TBI, [2][3][4][5] it becomes evident that differential DoC diagnoses, based solely on neurobehavioral testing, will result in a proportion of inaccurate diagnoses, thereby providing an inadequate empirical foundation for evidence-based neurorehabilitation. The long-standing problem of diagnostic inaccuracy 6,7 highlights the need for phenotypes of who will/will not progress from a vegetative state (VS) to the minimally conscious state (MCS) relative to emergence from MCS (eMCS).…”
mentioning
confidence: 99%
“…Specifically, severe TBI triggers pathological cellular processes (eg, excitotoxicity), thought to be active through chronic recovery phases, causing excitotoxicity, apoptosis, inflammatory events, seizures, demyelination, white matter pathology, and diminished neurogenesis, all of which are correlated with persisting neurobehavioral impairments. [2][3][4][5] For clinical neurorehabilitation research and practice, miRNAs are particularly promising because humans have more than 2500 miRNAs regulating 30% to 60% of messenger RNAs. [16][17][18][19][20] In addition, 70% of miRNAs are thought to be specific to the brain, spinal cord, and nerves.…”
mentioning
confidence: 99%
See 1 more Smart Citation